(untitled) (American Journal of Medical Science and Innovation, 2023)
Pregnant women with malaria and other associated infections have an increased risk of developing anemia later in pregnancy. This study aimed to determine the effect of mobile phone tele-reminder delivered through phone calls and SMS on the prevalence of malaria infection during pregnancy. The study recruited 150 pregnant women seeking antenatal care for the first time at the Phebe and Charles B. Dunbar hospitals in Bong County, Liberia. The antenatal care screening room (units of randomization) in both hospitals were randomized into six clusters. The 150 pregnant women were randomly assigned to an intervention group and a control group. A binary logistic regression using a generalized estimating equation model was run with a 95% Confidence Interval (CI). Malaria prevalence and antenatal care satisfaction were the primary outcome variables. The secondary outcome variable was the prevalence of anemia. Although there was a reduction in malaria infection in both groups, malaria prevalence between the intervention and control groups was not statistically significant (5 vs. 15%) (OR, 1.15; 95% CI, 0.71-1.85). Pregnant women in the intervention group were 4 times more likely to be very satisfied with ANC services compared with the control group (aOR, 4.01; 95%CI, 1.72-9.53). There was a positive trend toward anemia reduction among those in the intervention group. Integrating mobile phone technology in antenatal care services may help reduce the malaria infection rate and increase ANC satisfaction levels.